A comparative analysis of two land reform models, the Mashishimale farm management model and the Nkumbuleni strategic partnership model, South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2013)
Dissertation (MSc (Agric))--University of Pretoria, 2012.